2022
DOI: 10.1146/annurev-devpsych-121020-023312
|View full text |Cite
|
Sign up to set email alerts
|

Human Morality Is Based on an Early-Emerging Moral Core

Abstract: Scholars from across the social sciences, biological sciences, and humanities have long emphasized the role of human morality in supporting cooperation. How does morality arise in human development? One possibility is that morality is acquired through years of socialization and active learning. Alternatively, morality is instead based on a “moral core”: primitive abilities that emerge in infancy to make sense of morally relevant behaviors. Here, we review evidence that infants and toddlers understand a variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 118 publications
(101 reference statements)
2
25
0
Order By: Relevance
“…Despite some failures to replicate these findings (Salvadori et al., 2015; Schlingloff et al., 2020), a meta‐analysis of experiments probing early social evaluations found that infants and toddlers demonstrate a significant preference for prosocial over antisocial agents (Margoni & Surian, 2018). Since this meta‐analysis, 13 additional studies have provided evidence that infants and toddlers evaluate agents based on their social actions (see Woo et al., in press), consistent with the hypothesis that infants and toddlers prefer agents who help others to achieve their goals. Margoni and Shepperd (2020) have found, moreover, that the failed replications in this literature are consistent with the expected levels of error (i.e., false negatives) that occur when many samples are drawn from a population whose evaluations show a true preference for prosocial agents.…”
Section: Introductionsupporting
confidence: 67%
“…Despite some failures to replicate these findings (Salvadori et al., 2015; Schlingloff et al., 2020), a meta‐analysis of experiments probing early social evaluations found that infants and toddlers demonstrate a significant preference for prosocial over antisocial agents (Margoni & Surian, 2018). Since this meta‐analysis, 13 additional studies have provided evidence that infants and toddlers evaluate agents based on their social actions (see Woo et al., in press), consistent with the hypothesis that infants and toddlers prefer agents who help others to achieve their goals. Margoni and Shepperd (2020) have found, moreover, that the failed replications in this literature are consistent with the expected levels of error (i.e., false negatives) that occur when many samples are drawn from a population whose evaluations show a true preference for prosocial agents.…”
Section: Introductionsupporting
confidence: 67%
“…The infants in these studies preferentially reached for and looked to agents whose actions brought about the goal states that the protagonist desired, by pushing the agent up a hill that it had struggled to climb, opening the box that it had struggled to open, or returning its ball (Margoni & Surian, 2018;Woo et al, 2022;cf. Schlingloff et al, 2020).…”
Section: Who Help Othersmentioning
confidence: 99%
“…In these studies, infants viewed puppet show displays depicting protagonists who attempted to climb a hill (Hamlin et al, 2007, 2010), open a box containing a toy (Hamlin & Wynn, 2011; Steckler et al, 2017), or seek to recover a ball with which they had been playing (Hamlin & Wynn, 2011). The infants in these studies preferentially reached for and looked to agents whose actions brought about the goal states that the protagonist desired, by pushing the agent up a hill that it had struggled to climb, opening the box that it had struggled to open, or returning its ball (Margoni & Surian, 2018; Woo et al, 2022; cf. Schlingloff et al, 2020).…”
Section: Developmental Changes In Hierarchical Action Planning and Go...mentioning
confidence: 99%
“…The looking preference trial was followed by the critical reaching preference trial. Following the procedure of past studies of infant social evaluation ( 8 , 15 , 16 , 30 , 31 ), an experimenter who was unaware of the condition (imitation by mother vs. stranger) or of the particular puppet that the adult had imitated presented the real puppets to the infant, one in each hand, and asked, “Which one do you like?” We preregistered the prediction that infants would preferentially reach for the target of their own parent’s imitation. Indeed, most infants (11/14) reached for the puppet that their parent had imitated.…”
Section: Resultsmentioning
confidence: 99%
“…The home environments of the infants in the current sample likely include many representational toys, including puppets and dolls. Prior research shows that toddlers from this population are willing and able to treat puppets as social partners and interactions with puppets as socially meaningful events ( 14 , 30 ).…”
Section: Discussionmentioning
confidence: 99%